Terapi Bermain Kelompok untuk Meningkatkan Keterampilan Sosial pada Anak Disabilitas intelektual Ringan : Sebuah Studi Kasus - Ria Wiyatfi Linsiya; Renalatama Kismawiyati (Universitas Muhammadiyah Jember, 2023)
Children with intelectual dissability often experience obstacles in their social skills. This will affect the development of children, especially those related to relationships with other people which are feared to cause impacts such as loneliness and isolation. This study aims to train childrens’s social skills with group play therapy. Group play therapy is predicted to improve children’s social skills because it involves group activities. The approach in the research used is a qualitative approach with a casestudy reasearch method with single subject. The data colletion process was carried out using interviews, observation and documentation. The subject in this study was a child with mild mental retardation. The results showed that group play therapy can improve social skills in children with mild mental retardation which involves interaction with peers and participation in playgroups.